Komunitas Islami Sebagai Ruang Pertumbuhan Identitas Dan Kesehatan Psikologis Gen Z Urban Palembang - al kahfi (Jurnal Matlamat Minda : Manajemen Dakwah, 2025)
Urban Generation Z in Palembang faces increasingly fluid and flexible religious identity dynamics in response to the pressures of city life, intense digital exposure, and the demand for more freedom of self-expression. In this context, Islamic communities emerge as social spaces that not only provide religious activities but also serve important psychological functions for the development of this generation. This study aims to describe how Islamic communities contribute to shaping religious identity, providing emotional support, and strengthening the psychological well-being of urban Generation Z in Palembang. Using a descriptive qualitative method, data were collected through in-depth interviews and observations in several active Islamic communities with significant engagement with young people in Palembang. The results show that Islamic communities serve as platforms for Generation Z to find meaning in life, reinforce spiritual values, reduce psychological stress caused by urban pressures, and build emotionally safe social networks. Moreover, these communities help them cope with tendencies such as FOMO, confusion about life direction, and emotional instability that often arise in fast-paced digital life. Islamic communities also provide spaces for self-actualization through creative activities, preaching, mentoring, and peer support. This study concludes that Islamic communities play a significant role as supportive ecosystems for the psychological health and religious identity development of urban Generation Z, and they are relevant to be developed as models for religious guidance in increasingly complex digital and urban contexts.